The Nanomedicine Revolution - Wasim Alamgir; Adnan Haider (Life and Science)
Nanomaterials (NMs) have gained importance in technological advancement due to their changeable chemical, biological, and physical properties with improved efficacy compared to their bulk form. NMs are categorized according to their composition, size, shape, and origin with sizes ranging from 1 to 100 nm.1 NMs are being widely investigated for their potential use in  Nanomedicine, a multifaceted field where biological sciences intersect with nanoscience, nanoengineering and nanotechnology.